Effect of a chitosan edible‐coating enriched with Citrus limon peel extracts and Ocimum tenuiflorum leaf extracts on the shelf‐life of bananas. Issue 4 (3rd December 2020) - Deb Majumder, Samarpan; Sarathi Ganguly, Soumya
Abstract : In recent years, the need for the capability of decelerating the ripening process has increased significantly, especially in countries such as India where the post‐harvest loss is ∼630 billion dollars annually. The ripening process primarily starts with transpiration and respiration through microscopic pores present on the fruit. Accordingly, edible coatings can act as barriers, reducing the acceleration of these biochemical processes and enhance the shelf‐life of the fruit. For this study, 2% chitosan enriched with peel extracts from Citrus limon and leaf extracts from Ocimum tenuiflorum were used as an edible coating and the quality of bananas was evaluated over time. The ripening process was found to be delayed for a significant amount of time. The study also revealed increased anti‐oxidant activity based on absorbance changes of 2, 2‐diphenyl‐1‐picrylhydrazyl, which correlated with the phytochemical content of the fruit.